Potensi of Tobacco Stem Insecticide as Pest Control in Crops - Wahyuni, Srilah Nora; Sudarmawan, A. A.; Sudantha, I Made (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Tobacco is one of the most widely cultivated commodities in West Nusa Tenggara (NTB), especially Virginia tobacco. The leaf part is utilized as the main raw material in the cigarette industry. However, other parts of the plant, such as tobacco stems, are generally not used and only become agricultural waste that has no economic value, and has the potential to pollute the environment. In fact, tobacco stems have great potential as a vegetable insecticide that has proven effective in controlling various types of pests. This study aims to explore the potential of tobacco stems as a vegetable insecticide in pest control. The method used is a literature review by referring to various sources, including scientific journals, books, news, and related research and implementation. The results showed that tobacco stems contain secondary metabolite compounds, such as nicotine, saponins, flavonoids, and terpenoids. These compounds function as contact poisons, repellents, and disruptors of pests' metabolic, nervous, and respiratory systems. As a result, these compounds can cause body damage, inhibit the life cycle, and even death in insect pests, such as Aphis sp. aphids, Bemisia tabaci, Plutella xylostella, and other pests. In conclusion, tobacco stem extract is an effective solution for controlling pests in cultivated plants. Its use can reduce the population and intensity of pest attacks due to the content of chemical compounds that are toxic to insects.